The Research Project Assessing Prospective Novel Pedagogical Strategies For Music Education In Higher Education - Wei, Zhang; Paramalingam, Muhantha (Journal of Neonatal Surgery, 2025)
More and more people throughout the world are beginning to see the merit in music pedagogy and systematic instruction. Organized piano lessons may help bring together the academic world and the non-professional piano teaching sector since they are based on research-based and well-informed training. Furthermore, the research delves into how these assessments of the suitability of their piano training might influence how they use a range of piano skills while teaching pupils in a classroom environment. The researcher used a questionnaire that comprised a total of twelve separate practical piano abilities. These skills included a wide range of areas, including improvising, sight reading, accompaniment, composition, score eating literature, methods, melodic progressions, harmonisation, transposition, and modulation. The connections between music education and virtue, people, mental health, cognitive growth, and creative problem-solving are examined in this research. In order to probe these associations, the study used quantitative data. These findings provide further support to the concept that musical exposure greatly enhances children's general competence. Based on the quantitative analysis that was conducted in this research to evaluate the relationships between music training and various individual talents, the hypothesis is given increased weight. The study fills up the gaps left by previous research that did not include a quantitative examination of music education. Researchers also provide important suggestions for how colleges and universities may get more involved, develop more comprehensive curricula, and conduct more thorough evaluations of this field.